Análisis de los textos escolares del ministerio de educación en relación con el entorno socioeducativo en la escuela “Primero de Mayo” de la parroquia Juan Montalvo, cantón Latacunga - Ordoñez Viera, Edilma Soledad (2016)
The general objective of this research was to analyze the official texts of the Ministry of Education, through strategies to relate the content with the social environment to improve educational quality at Primero de Mayo School during the academic year 2015-2016. Since, the research problem was: What strategies would teachers use to analyze the official texts of the Ministry of Education in Relation with the socio-educational environment at Primero de Mayo School in Juan Montalvo Parish, Latacunga canton? The deductive and inductive methods were used; the first for the theoretical study of the research variables and the second for the formulation of conclusions based on analysis and Interpretation of Results….